Resveratrol Regulates the Expression of Genes Involved in CoQ Synthesis in Liver in Mice Fed with High Fat Diet - Catherine Meza-Torres; Juan Diego Hernández-Camacho; Ana Belén Cortés-Rodríguez; Luis Fang; Tung Bui Thanh; Elisabet Rodríguez-Bies; Plácido Navas; Guillermo López-Lluch (MDPI AG, 2020)
Resveratrol (RSV) is a bioactive natural molecule that induces antioxidant activity and increases protection against oxidative damage. RSV could be used to mitigate damages associated to metabolic diseases and aging. Particularly, RSV regulates different aspects of mitochondrial metabolism. However, no information is available about the effects of RSV on Coenzyme Q (CoQ), a central component in the mitochondrial electron transport chain. Here, we report for the first time that RSV modulates COQ genes and parameters associated to metabolic syndrome in mice. Mice fed with high fat diet (HFD) presented a higher weight gain, triglycerides (TGs) and cholesterol levels while RSV reverted TGs to control level but not weight or cholesterol. HFD induced a decrease of COQs gene mRNA level, whereas RSV reversed this decrease in most of the COQs genes. However, RSV did not show effect on CoQ9, CoQ10 and total CoQ levels, neither in CoQ-dependent antioxidant enzymes. HFD influenced mitochondrial dynamics and mitophagy markers. RSV modulated the levels of PINK1 and PARKIN and their ratio, indicating modulation of mitophagy. In summary, we report that RSV influences some of the metabolic adaptations of HFD affecting mitochondrial physiology while also regulates COQs gene expression levels in a process that can be associated with mitochondrial dynamics and turnover.